Foreign aid, fertility and populations growth: Evidence from Africa - Leonid V. Azarnert (Bar-Ilan University, Department of Economics, 2009)
This article investigates the relationship between foreign aid and population growth in sub-Saharan Africa. The work considers population growth rate and a directly related to fertility demographic indicator - total fertility rate. Using a panel of 43 African countries over the last four decades of the 20th century, it demonstrates the positive association between foreign aid and population growth and suggests that foreign aid affects population growth primarily through its effect on fertility. These findings suggest that the appreciation of the demographic effect of foreign aid can have important implications for the design of policies regarding to foreign aid for presently developing countries, particularly in sub-Saharan Africa.
Keywords: F35; J11; O11; 330; Foreign aid; Fertility; Population growth; Entwicklungshilfe; Fertilität; Bevölkerungswachstum; Humankapital; Bildungsinvestition; Afrika südlich der Sahara